A139 ASYMPTOMATIC IBD IS A COMMON FINDING IN FIT POSITIVE INDIVIDUALS. (1st March 2018) - Quinlan, J; Borgaonkar, M; Antle, S; Pace, D; McGrath, J S
Abstract: Background: Inflammatory Bowel Disease is often present for months and even years before a formal diagnosis is made. This time represents a missed opportunity for early intervention that may have a significant impact on disease course and prevent unnecessary surgeries. Aims: The purpose of this study was to assess findings of undiagnosed IBD within Newfoundland and Labrador from the provincial colon cancer screening program. Methods: Data for this study was obtained in a prospective fashion using the Newfoundland and Labrador Colon Cancer Screening Program. Those enrolled in the study were between the ages of 50–74 at average risk for colon cancer. Between July 1, 2012 and June 30, 2016, participants were provided with two FIT tests – if a minimum of one test was ≥100ng/mL, participants were further evaluated via colonoscopy. Data on the patient's age, gender, FIT value, presence of adenoma, pathology, and other variables were collected. Results: Of the 21, 371 FIT kits mailed out, 16, 152 (75.6%) were returned, of which, 2694 (16.7%) had at least one FIT value ≥100ng/mL. At the time of analysis, 1831 participants had been further evaluated by colonoscopy. Colonoscopy identified 35 patients (1.9%) with undiagnosed inflammatory bowel disease, confirmed by pathology. Of those found to have IBD, 57.1% were female, 42.9% were male, and 54.3% had two positive FIT values. The age of those with IBD ranged from 50–71 with a mean of 59.5. The highest FIT value of those with IBD ranged from 100.0 to 18877.0 with a mean of 2048.1, 25 th percentile of 180, 50 th percentile of 518, and 75 th percentile of 1463. For comparison, the mean highest FIT value for those with colon cancer was 4219.8, for those with an adenoma was 1140.2 and for those with no finding was 580.4. Conclusions: This study shows that undiagnosed inflammatory bowel disease in the fifth to seventh decade of life is not an uncommon occurrence. The prevalence of diagnosed IBD in Canada is estimated to be 0.428%, with 0.194% having ulcerative colitis and 0.234% having Crohn's disease. Of the 16, 152 participants who returned their FIT test, 0.27% were found to have undiagnosed IBD. These findings suggest that there is a substantial burden of undiagnosed IBD in Newfoundland and Labrador. Funding Agencies: None